1985
DOI: 10.1111/j.1365-2605.1985.tb00836.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphological factors influencing the penetration of human sperm into cervical mucus in vitro

Abstract: The efficiency of cervical mucus in filtering out single, multiple and associated abnormalities of human spermatozoa was determined. Twenty semen samples which gave a normal in vitro cervical mucus penetration test (CMPT) were analysed before and after migration using a detailed classification system (13 categories). The % of normal forms was significantly increased in cervical mucus (59.5 vs 33.2%), whereas the % of sperm with single, multiple or associated abnormalities of the midpiece or of the flagellum we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0
1

Year Published

1988
1988
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 12 publications
3
13
0
1
Order By: Relevance
“…MacLeod and Gold (1951) have already shown that in natural fertilization spermatozoa morphology of infertile men is different from that of fertile men; Jouannet et al (1981) found that morphology is the sperm parameter that makes the best distinction between infertile and fertile populations of men. Jeulin et al (1985) confirmed that the cervical mucus selects the spermatozoa in function of its morphology: spermatozoa with abnormalities in the principal or middle pieces of the tail either isolated or associated with head abnormalities, are stopped by the mucus. Rogers et al (1983) found that the percentage of normal shapes is the sperm factor with the highest correlation with the hamster oocyte fertilization rate.…”
mentioning
confidence: 74%
“…MacLeod and Gold (1951) have already shown that in natural fertilization spermatozoa morphology of infertile men is different from that of fertile men; Jouannet et al (1981) found that morphology is the sperm parameter that makes the best distinction between infertile and fertile populations of men. Jeulin et al (1985) confirmed that the cervical mucus selects the spermatozoa in function of its morphology: spermatozoa with abnormalities in the principal or middle pieces of the tail either isolated or associated with head abnormalities, are stopped by the mucus. Rogers et al (1983) found that the percentage of normal shapes is the sperm factor with the highest correlation with the hamster oocyte fertilization rate.…”
mentioning
confidence: 74%
“…However, this selection is limited and does not exclude all the abnormal forms, in particular spermatozoa with abnormal heads (Ahlgren et al, 1974;Mortimer et al, 1982). In vitro, cervical mucus penetration tests show that some abnormal spermatozoa, such as those with small oval and pyriform heads, can penetrate the mucus as well as normal spermatozoa (Jeulin et al, 1985). The morphology status of human spermatozoa at the fertilization sites in vivo is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…However, we may speculate on it. It is known that sperm motility characteristics (15,16), their head shape (17,18), and their acrosomal activity (19) are of major importance in the migration and penetration processes. Therefore, we can assume that normally shaped motile spermatozoa with large nuclear vacuoles will probably be able to pass through the female tract barriers and proceed to fertilize the female egg.…”
Section: Figurementioning
confidence: 99%